Grammatical Errors Produced by UGM English Department Students - Ikhwanuddin Hasan; Aris Munandar (Lexicon, 2018)
This research attempts to identify the grammatical errors produced by students of the English Department of UGM year 2012 in their final paper of the writing class. In particular, it attempts to classify the errors based on Surface Strategy Taxonomy proposed by Dulay, Burt, and Krashen (1982). The data used in this research were taken from the submitted assignments of the English Department students of Universitas Gadjah Mada year 2012 in General English, particularly nine students in writing class. We found 178 errors in fourteen linguistic categories which are divided into four parts: omission, addition, misformation, and misordering. From all the four parts, we discovered that the most frequent errors found are in the part of misformation (97 errors; 54.49%), followed by omission (38 errors; 31.11%), misordering (22 errors; 12.78%), and addition (20 errors; 11.11%). However, in the linguistic categories, the three most frequent errors found are misformation of verbal (30 errors), misordering of complex sentence (20 errors), and omission of determiner (19 errors).